2022
DOI: 10.3390/ijms232314970
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Faceted Roles of DNAJB Protein in Cancer Metastasis and Clinical Implications

Abstract: Heat shock proteins (HSPs) are highly conserved molecular chaperones with diverse cellular activities, including protein folding, assembly or disassembly of protein complexes, and maturation process under diverse stress conditions. HSPs also play essential roles in tumorigenesis, metastasis, and therapeutic resistance across cancers. Among them, HSP40s are widely accepted as regulators of HSP70/HSP90 chaperones and an accumulating number of biological functions as molecular chaperones dependent or independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…As such non-native, aggregation-prone folds are typical clients of molecular chaperones, we screened for JDPs that specifically recognize and then prevent the misfolding and aggregation of two destabilizing, cancer-associated hot-spot p53 mutants - R249S and R282W. Four main classes of JDPs, previously reported to affect cancer progression, were tested: class A (DNAJA1 and DNAJA2), class B (DNAJB1 and DNAJB4), non-canonical class B (DNAJB2 and DNAJB6), and class C (DNAJC7 and DNAJC8) chaperones 3, 13, 14 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As such non-native, aggregation-prone folds are typical clients of molecular chaperones, we screened for JDPs that specifically recognize and then prevent the misfolding and aggregation of two destabilizing, cancer-associated hot-spot p53 mutants - R249S and R282W. Four main classes of JDPs, previously reported to affect cancer progression, were tested: class A (DNAJA1 and DNAJA2), class B (DNAJB1 and DNAJB4), non-canonical class B (DNAJB2 and DNAJB6), and class C (DNAJC7 and DNAJC8) chaperones 3, 13, 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Conformational p53 oncogenic mutants are misfolding-prone clients of the chaperone system. Specifically, several JDP family members were described to promote cancer by acting on these destabilized mutant proteins, preventing p53 ubiquitination and degradation 3, 13, 14 . Here we identified a previously uncharacterized client binding domain in class A JDPs, which can recognize the initial stages of misfolding in p53 mutants and, via direct interaction, stabilize the β-sheet rich DNA-binding domain in these oncoproteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, we demonstrated that miR‐23a‐3p bound to DNAJB1 complementally. DNAJB1, located at 19p13.2, plays an important role in protein translation, folding/refolding, transport, and degradation 27 . DNAJB1‐PRKACA fusion transcripts are considered to be oncogenic drivers of fibrolamellar hepatocellular carcinoma 28 .…”
Section: Discussionmentioning
confidence: 99%